Arthur's Halloween - Brown, Marc Tolon (Boston : Little, Brown, 1982)
Arthur finds everything about Halloween scary, including his little sister's costume, his morning snack, and the big house on the corner.
430
430
Accelerated Reader AR
Keywords: Halloween -- Fiction; Animals -- Fiction